Central American Alliance for Sustainable Development - IICA (IICA San JoseCR, 1996)
Includes the documents issued at three meetings of Central American presidents: the Declaration of Guacimo...1994; the Central American Ecological Summit for Sustainable Development...Managua, Nicaragua... 1994; and, the International Conference on Peace and Development in Central America...Tegucigalpa, Honduras...1994. Presents a comprehensive strategy for the region in the Central American Alliance for Sustaniable Development.